Sistem Informasi Tempat Wisata Pada Aplikasi Berbasis Android - Pribadi, Adi Wahyu; Salsabila, Daniza (Universitas Pancasila, 2023)
The government provides encouragement for tourism actors to develop their businesses in order to maintain the tourism sector which has succeeded in exceeding the target. However, tourism actors lack the management knowledge to take advantage of opportunities that affect the image of tourist attractions. Therefore, this research is based on the results of a literature study and a questionnaire that focuses on the purpose of providing an Android-based platform for tourism owners and tourists called PergiJalan. According to the results of the system development evaluation using the SDLC Waterfall research method, it can be concluded that this application has succeeded in providing a very good experience and service for tourism actors.